Human IgE is efficiently produced in glycosylated and biologically active form in lepidopteran cells. (April 2016) - Bantleon, Frank; Wolf, Sara; Seismann, Henning; Dam, Svend; Lorentzen, Andrea; Miehe, Michaela; Jabs, Frederic; Jakob, Thilo; Plum, Melanie; Spillner, Edzard
Highlights: Human IgE is efficiently expressed and secreted by lepidopteran insect cells. The complex glycosylation of the recombinant IgE is shifted toward pauci- and oligomannosidic structures without impairment of function. The complex-type glycans appear to be dispensable for structure and function. Abstract: TH 2-biased immunity to parasites and allergens is often associated with increased levels of antigen-specific and high affinity IgE. The role in reacting against minute amounts of target structures and to provoke severe anaphylactic reactions renders IgE a mechanistically outstanding isotype. IgE represents the least abundant serum antibody isotype and exhibits a variety of peculiarities including structure, extensive glycosylation and effector functions. Despite large progress in antibody technologies, however, the recombinant access to isotypes beyond IgG such as IgE still is scarce. The capacity of expression systems has to meet the complex structural conformations and the extensive posttranslational modifications that are indispensable for biological activity. In order to provide alternatives to mammalian expression systems with often low yield and a more complex glycosylation pattern we established the recombinant production of the highly complex IgE isotype in insect cells. Recombinant IgE (rIgE) was efficiently assembled and secreted into the supernatant in yields of >30 mg/L. Purification from serum free medium using different downstream processing methods provided large amounts of rIgE. This exhibited a highly specific interaction with its antigen, therapeutic anti-IgE and its high affinity receptor, the FcεRI. Lectins and glyco-proteomic analyses proved the presence of prototypic insect type N -glycans on the epsilon heavy chain. Mediator release assays demonstrated a biological activity of the rIgE comparable to IgE derived from mammalian cells. In summary the expression in insect cells provides rIgE with variant glycosylation pattern, but retained characteristics and biological activity. Therefore our data contribute to the understanding of functional and structural aspects and potential use of the IgE isotype.